TNNI3K delays atrioventricular conduction and reduces connexin-45 gap junctional coupling. (19th May 2022) - Pham, C; Podliesna, S; Verkerk, AO; Wolswinkel, R; Munoz-Martin, N; Veldkamp, MW; Beekman, L; Wilde, LMW; Remme, CA; Bezzina, CR; Lodder, EM
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The Dutch Research Council (NWO Talent Scheme) Introduction: Cardiac conduction delay is the main substrate for triggering arrhythmias. Hence, prolongation of the PR interval on the electrocardiogram (ECG) is a strong predictor of atrial fibrillation, the most common cardiac arrhythmia. In previous research, cardiac troponin I-interacting kinase (TNNI3K) has been identified as a regulator of the PR interval. Various inbred mouse strains showed a correlation between Tnni3k expression levels and PR interval durations. Additionally, transgenic mice overexpressing hTNNI3K presented an extreme PR interval prolongation. Objective: This study aims to unravel the mechanism underlying TNNI3K-driven PR interval prolongation. Methods: ECG parameters were recorded in mice expressing physiological levels of Tnni3k (congenic), overexpressing hTNNI3K (TNNI3Ktg), or overexpressing kinase-dead hTNNI3K (TNNI3K-KDtg) and were compared to low-Tnni3k expressing DBA/2J control mice. Atrioventricular (AV) conduction was measured in Langendorff-perfused isolated hearts by electrical mapping. Cellular electrophysiology and conductance were measured using the (dual) patch-clamp technique. AV nodal collagen levels were identified by Pico Sirius Red staining. Candidate interactors were identified by immunoprecipitation of transfected HEK293A cell lysates. In stable HeLa-Connexin 45 (Cx45) cell lines expressing TNNI3K, Cx45 protein expression and phosphorylation levels were investigated by Western blot. Localisation of Cx45 was characterised by immunofluorescence. Results: At six weeks of age, congenic and TNNI3Ktg mice show a 17% and 35% prolonged PR interval duration, respectively. Nonetheless, the PR interval of TNNI3K-KDtg mice did not change. Electrical mapping experiments on TNNI3Ktg mouse hearts show a corresponding AV conduction delay, which was neither driven by changes in cellular atrial cardiomyocyte electrophysiology nor driven by AV-nodal fibrosis. We next identified Cx45, a highly expressed connexin in the AV node, as a potential TNNI3K interactor. HeLa-Cx45 cells expressing TNNI3K demonstrated a reduced Cx45 conductance compared to controls without changes in kinetics. Moreover, we observed relatively decreased Cx45 phosphorylation and increased Cx45 intracellular accumulation. Conclusion: We here present TNNI3K as a kinase-driven modulator of PR interval prolongation and AV conduction delay, which is independent of atrial electrophysiology and AV nodal fibrosis. We further identified Cx45 as a novel interactor of TNNI3K. The presence of TNNI3K reduces Cx45 gap junctional conductance and promotes intracellular Cx45 protein accumulation, which could explain the PR interval prolongation in vivo. Altogether, this study implies a crucial role for TNNI3K in AV nodal conduction.